Combined PET/CT-perfusion in patients with head and neck cancers might predict failure after radio-chemotherapy: a proof of concept study. Issue 1 (December 2015) - Pietsch, Carsten; de Galiza Barbosa, Felipe; Hüllner, Martin; Schmid, Daniel; Haerle, Stephan; Huber, Gerhard; Studer, Gabriela; Hany, Thomas; Veit-Haibach, Patrick
Abstract Background [18F]FDG-PET/CT imaging is broadly used in head and neck cancer (HNSCC) patients. CT perfusion (CTP) is known to provide information about angiogenesis and blood-flow characteristics in tumors. The aim of this study was to evaluate the potential relationship of FDG-parameters and CTP-parameters in HNSCC preand post-therapy and the potential prognostic value of a combined PET/CT with CTP. Methods Thirteen patients with histologic proven HNSCC were prospectively included. All patients underwent a combined PET/CT with integrated CTP before and after therapy. Pre- and post-therapeutic data of CTP and PET of the tumors were compared. Differences were tested using Spearman's rho test and Pearson's correlation. Ap -value ofp <0.05 was considered statistically significant. Correlations were calculated using Pearson's correlation. Bootstrap confidence intervals were calculated to test for additive confidence intervals. Results Three patients died due to malignancy recurrence, ten patients were free of recurrence until the end of the follow-up period. Patients with recurrent disease had significantly higher initial CTP-values compared to the recurrence-free patients: BFpre 267.4 (171.2)ml/100 mg/min, BVpre 40.9 (8.4)ml/100 mg and MTTpre 8.2 (6.1)sec. No higher SUVs initially but significantly higher TLG compared to patients without recurrence were found. Post-therapeutic PET-values differed significantly between the two groups: SUVmaxpost 6.0 (3.2), SUVmeanpost 3.6 (2.0) and TLG 21751.7 (29794.0). Conclusion In our proof of concept study, combined PET/CT with integrated CTP might show complementary prognostic data pre- and post chemo-radiotherapy. CTP may be used to predict local tumor recurrence, while FDGPET/CT is still needed for whole-body staging.